Phenolic Content and Antioxidant Capacities at Different Stages of Berangan Banana Ripening - Shahdan, Surinawati; Majaliwa, Nuria; Nyamete, Frida; Omar, Nor Adila Mhd (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
Bananas are widely consumed for their nutritional value, but the optimal ripening stage for maximizing health benefits remain unclear. This study investigated the total phenolic content (TPC) and antioxidant capacities of Berangan bananas across seven ripening stages. TPC was measured using the Folin-Ciocalteu assay with gallic acid as the standard, while antioxidant activities were evaluated via 2,2-diphenyl1-picryl-hydrazyl-hydrate (DPPH) and cupric reducing antioxidant capacity (CUPRAC) assays, with ascorbic acid as the standard. Results indicated that stages 1 (8.543±0.268 mg GAE/g), 2 (8.646±0.034 mg GAE/g), and 7 (8.99±0.059 mg GAE/g) had the highest phenolic content, while stage 5 had the lowest (6.756±0.069 mg GAE/g). The strongest DPPH scavenging activity was observed at stages 5 and 6, with IC50 values of 25.92 μg/mL and 25.28 μg/mL, respectively. The highest CUPRAC value was found at stage 2, measuring 34.027±0.027 mg AAE/g at 100 μg/mL. These findings suggest that bananas consumed at different ripening stages offer varying antioxidant benefits, which could influence dietary choices for optimal health. This study highlights the therapeutic potential of bananas as a functional food, providing natural antioxidants that beneficial consumer health and nutrition. Further research may expand on these findings to explore therapeutic applications of banana antioxidants.